2022
DOI: 10.3390/md20030167
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action and Therapeutic Potential of the β-Hairpin Antimicrobial Peptide Capitellacin from the Marine Polychaeta Capitella teleta

Abstract: Among the most potent and proteolytically resistant antimicrobial peptides (AMPs) of animal origin are molecules forming a β-hairpin structure stabilized by disulfide bonds. In this study, we investigated the mechanism of action and therapeutic potential of the β-hairpin AMP from the marine polychaeta Capitella teleta, named capitellacin. The peptide exhibits a low cytotoxicity toward mammalian cells and a pronounced activity against a wide range of bacterial pathogens including multi-resistant bacteria, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
(51 reference statements)
4
16
0
Order By: Relevance
“…The following subculturing with 3 passages (days) in the absence of the peptide showed that their final MICs were not changed. Notably, polymyxin B rapidly induced a stable resistance and displayed a 128-fold increase in the MIC value, which corresponded well to our previous results [ 21 ]. An important factor is that abarenicins do not induce a stable resistance of E. coli MDR Cl 1057 compared to the membrane-active polymyxin B, which has a similar mechanism of action.…”
Section: Resultssupporting
confidence: 91%
“…The following subculturing with 3 passages (days) in the absence of the peptide showed that their final MICs were not changed. Notably, polymyxin B rapidly induced a stable resistance and displayed a 128-fold increase in the MIC value, which corresponded well to our previous results [ 21 ]. An important factor is that abarenicins do not induce a stable resistance of E. coli MDR Cl 1057 compared to the membrane-active polymyxin B, which has a similar mechanism of action.…”
Section: Resultssupporting
confidence: 91%
“…After showing that GK-4 has strong antibacterial activity, we tried to further clarify its antibacterial mechanisms. As an important protective barrier for Gram-positive and Gram-negative bacteria, the bacterial cell membrane is usually the target of most AMPs [ 30 , 31 , 32 ]. In addition to the outer membrane, the cytoplasmic membrane is an important barrier in both Gram-positive and Gram-negative bacteria, PG, CL and PE are the main components of the cytoplasmic membrane, and PC mainly exists in eukaryotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…An example of this detergent like model is isoeugenol, which increases membrane fluidity, affects lipid packing, and induces membrane shape changes . Similarly, Safronova et al found that the peptide capitellacin plays its antimicrobial activity through a detergent like model. In addition, the K4 peptide (a de novo AMP) also displays a detergent like mechanism for its antimicrobial activity …”
Section: Activity Mechanisms Of Milk Protein Derived Ampsmentioning
confidence: 99%